Homeopathy in the Treatment of Cancer: A Hope That Must Be Nurtured - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2024)
Homeopathy is a clinical methodology discovered by the Saxon physician Samuel Hahnemann and is based on the law of similarity according to which "like cures like", therefore, substances are administered to the patient in small "ultradiluted", "infinitesimal" doses, taking into account that such substances, in high doses, in healthy individuals produce symptoms similar to those that must be fought in the patient. Homeopathy, over the course of about two centuries, has been harshly criticized because it uses excessively diluted doses and, even, drugs that do not contain any chemical active ingredient. In the ultradiluted homeopathic solution the active ingredient disappears, but it is conceivable that it is "memorized" by the solution, in fact, some scientific studies on the so-called "memory of water" explain, at least in part, the reasons why homeopathic drugs are effective. The effectiveness of homeopathic medicines has also been found in the treatment of cancer and some experiments, in vivo and in vitro, are truly enlightening because they highlight the cytotoxic effects of homeopathic ultradilutions on cancer cells. Although the experiments and scientific research on homeopathy must be further explored, although homeopathic medicines cannot replace chemotherapy, although the evidence must be completed with other evidence, some scientific studies allow us to seriously reflect on the therapeutic potential of homeopathic medicines, medicines that can be used in the treatment of serious diseases, including cancer. This is why we believe that homeopathy, in the treatment of cancer, is a hope that must be nurtured.